Evaluasi Pasca Pelatihan Kepemimpinan Nasional Tingkat II Pada Pemerintah Daerah Provinsi Papua - Stevanus Thane; Fauziah Faranita Farawowan; John Agustinus (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of the Post-Training Evaluation activity is to gather information for further improvement of the training program. While the specific purpose of implementing the Post-Training Evaluation for alumni of the National Leadership Training Level II Class XXVI of 2022 is to find out: changes in the attitude of alumni behavior in carrying out their duties and positions Impact of the National Leadership Training on performance, and Sustainability of PKN Level II policy brief recommendations. The method used in the post-training PKN II Batch XXVI 2022 evaluation carried out by BPSDM Papua Province, is to use the Expert Judgment model. This evaluation model is carried out by involving universities as evaluators and BPSDM employees to analyze the post-training evaluation process with the aim of identifying strengths and weaknesses in aspects related to post-training evaluation. Conclusion: Implementation of PKN Level II Batch XXVI in 2022 is in the Good and Very Good category. The results of the training were implemented by the participants which were manifested in the form of change projects and policy briefs in accordance with the tasks and functions and themes of PKN Level II determined by LAN, in the implementation of change projects there is superior support, availability of resources and support from external parties. Recommendations given to training managers include: Environmental support that is not in favor of the Alumni Action for Change, Evaluation after PKNT Level II Batch XXVI can be used as information material on the sustainability of the policy brief recommendations for LAN RI as the person in charge of PKN II activities, must be committed to the participants and Mentors but can be realized consistently well after the training.